2021
DOI: 10.3390/app11167463
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Antimicrobial Effect of an Ethanolic Extract of Propolis in Periodontal Disease

Abstract: Periodontal disease encompasses gingivitis and periodontitis and is one of the most common chronic infections in the adult population. This study aimed to evaluate the influence of Spanish propolis extract (EEP) on the effect of the clinical and microbiological parameters as an adjuvant to scaling and root planning in patients undergoing supportive periodontal therapy (SPT). Forty chronic periodontitis patients were randomly assigned into two groups for the treatment. In the control group (n = 20), the sites w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Antibacterial action of propolis is connected with the presence of flavonoids such as galangin, chrysin, pinobanksin, quercetin, naringenin, apigenin, tt-farnesol as well as phenolic acids like caffeic acid, benzoic acid, gallic acid, and cinnamic acid and bacarin or ursolic acid ( Table 1 ) [ 7 , 8 , 9 , 10 ]. A study conducted by Lisbona-Gonzales et al confirmed that the ethanolic extract of Spanish Propolis reduced bacterial counts of Tannerella forsythensis and Porphyromonas gingivalis [ 11 ].…”
Section: The Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Antibacterial action of propolis is connected with the presence of flavonoids such as galangin, chrysin, pinobanksin, quercetin, naringenin, apigenin, tt-farnesol as well as phenolic acids like caffeic acid, benzoic acid, gallic acid, and cinnamic acid and bacarin or ursolic acid ( Table 1 ) [ 7 , 8 , 9 , 10 ]. A study conducted by Lisbona-Gonzales et al confirmed that the ethanolic extract of Spanish Propolis reduced bacterial counts of Tannerella forsythensis and Porphyromonas gingivalis [ 11 ].…”
Section: The Resultsmentioning
confidence: 99%
“…has been confirmed by Dziedzic et al, and Elbaz and Elsayad. The mentioned strains turned out to be responsible for the biofilm formation [ 11 , 53 ].…”
Section: The Resultsmentioning
confidence: 99%
See 3 more Smart Citations